Sistem Informasi Geografis Usaha Mikro Kecil Menengah (UMKM) di Kota Tanjungpinang berbasis Android - Aggry Saputra; Rhoelly Rizqianandha Tawaqal Rhoelly; Aurora Elsa Shafira Frederick (Jurnal Bangkit Indonesia, 2023)
The increasing economic growth in Tanjungpinang City, which is the main gateway for tourists who will visit various tourist destinations on the island of Bintan, has caused many Micro, Small and Medium Enterprises units to appear in the city of Tanjungpinang. According to data from the Tanjungpinang City Manpower Office, there are 14,687 Micro, Small and Medium Enterprises in Tanjungpinang city. However, the distribution map of the number of Micro, Small and Medium Enterprises is not known with certainty, so this makes it quite difficult for the government to provide assistance programs to Micro, Small and Medium Enterprises which are spread across the city of Tanjungpinang. This can be overcome if the Office of Manpower, Cooperatives and Micro Enterprises of Tanjungpinang City has an application that is able to visualize the distribution map of every Small and Medium Enterprises in Tanjungpinang City and is always up to date and uses an Android-based system and is integrated with the database. Designing Android-based applications using GPS will make it easier to map locations, in this case, UMKM in Tanjungpinang City. It is hoped that with this application, users and the government will find it easier to know the whereabouts of MSMEs and what products are occupied or produced by these MSMEs.